Detection early And Education about Hypertension on public in RT 19 Kelurahan Ricefield Wide New Bengkulu City - Suryani, Ade Irma; Salma , Atika; Daughter, Anisa Ika; Kartika, Goddess; Safitri , Devi; Hartati , Devi; Sari, Felia Novita; Sihombing, Ginna Veronica; Selviana, Indah; Sari, Nilam Kencana; Veronica, Syndi Ayu; Ningsih, Sunarti Maili; Yurnilawati, Yurnilawati; Novita, Vivin (Jurnal Inovasi Kerja Nyata, 2025)
Hypertension is a condition in which there is an abnormal and continuous increase in blood pressure on several examinations. Hypertension often causes changes in blood vessels that can result in higher blood pressure. Early treatment of hypertension is very important because it can prevent complications in several organs of the body such as the heart, kidneys, and brain. One of the actions that can be taken for blood pressure in hypertensive patients is through Benson relaxation. The purpose of this application is to help lower blood pressure in hypertensive patients through Benson Relaxation is a relaxation technique that combines deep breathing with elements of belief or spirituality. This technique was developed by Dr. Herbert Benson and involves deep breathing, muscle relaxation, and focusing on calming words or thoughts according to the individual's beliefs. The Thematic Real Work Lecture Program (KKN-T) of Dehasen University, Bengkulu aims to evaluate the effectiveness of health knowledge in improving community knowledge and practices through blood pressure checking activities, educational leaflets, health education, and group discussions. The results of this program show that most people have low knowledge about environmental health. This activity was carried out in the RT 19 settlement, this program shows an increase in public awareness of the importance of healthy living. recommends the implementation of this education program periodically by health workers and integrated health post cadres to create a healthy and independent society.